الوطنية في فلسفة محمد اقبال الشعرية: Patriotism in the Poetic Philosophy of Muhammad Iqbal - Dr Zaib Un Nisa (Al Manhal Research Journal, 2025)
Patriotism is the love and loyalty of an individual to his homeland, which includes the land, people, customs, traditions, and pride in the history of the homeland. Patriotism means to feel an association to the homeland, possessing national qualities, and loving the homeland. It instills a continuous passion in their souls for the homeland. It makes a person find peace in it, yearn for it when far from it, defend it when it is attacked, and get furious if someone betray it. It is noteworthy that we find patriotic poetic verses by poets in all nations and countries. Poets of the Arabian Peninsula and those of the Indian subcontinent, including Pakistani poets, did not lag behind in this field compared to the poets of other regions. They contributed with significant efforts and came up with precise descriptions of various elements of patriotism. Studying the aspect of patriotism in the poetry of Muhammad Iqbal is of particular importance. It motivates people towards revolution, greatness, and dignity, and fills their souls with hope. It also encourages leaving laziness, betrayal, servitude, humiliation, and insult.